Prevalensi gejala Infeksi Saluran Pernapasan Atas (ISPA) sesuai dengan polusi udara dan aktivitas fisik - Bahri, Samsul; Safei, Imam; Mulyawan, Rizki; Fahmi Hasan, Muhamad; Adriyani, Riza (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2023)
Air pollution is often associated with Upper Respiratory Infection (URI), and children are generally the most susceptible to URI. Although physical activity has a positive impact on health, it should be remembered that unhealthy pollution concentrations can eliminate the positive effects of physical activity. Thus, this research aimed to map the concentration of air pollution associated with the prevalence of URI symptoms and the level of physical activity in children throughout Java Island. This research uses a multicenter design, a descriptive quantitative method with a cross-sectional approach, within every six big cities on Java Island, Indonesia. The total subjects in this research were 1,216 male and female elementary school students from six provinces throughout Java Island (Banten, n=200), (Jakarta, n=200), (Bandung, n=202), (Semarang, n =210), (Yogyakarta, n=201), (Surabaya, n=203). Data was collected offline using the physical activity and URI questionnaires, accompanied directly by the original teacher. The research results indicated that unhealthy air pollution quality (> 35 µg/m³) was associated with the prevalence of URI symptoms (Jakarta 18.9% and Semarang 21.6%). Data analysis using ANOVA to see the interaction between 6 big cities and investigate within each city using paired t-test. Students' level of physical activity was related to air pollution, which could negatively impact the respiratory system. Therefore, these findings can be of particular concern to city governments and school teachers not to rule out the dangers of air pollution and the benefits of physical activity in schools.